MENUJU HUKUM YANG PROGRESIF DI INDONESIA - ENDANG YULIANA SUSILAWATI (Wacana Hukum, 2010)
Abstract The formulating and the issuing of judicial outcome are frequently inviting polemic within the society. Conflicts, controversies, and dilemmas must be tackled in careful manner. Keywords: judicial reform, progressive regulation.